2018
DOI: 10.1177/014556131809700612
|View full text |Cite
|
Sign up to set email alerts
|

Otosclerosis in a Nonendemic Population: Utility of CT Scan and Correlation with Audiometry and Surgical Outcome

Abstract: The incidence of otosclerosis in nonendemic patients is low, and preoperative diagnosis can be challenging. The aim of this study was to evaluate computed tomography (CT) findings in patients with otosclerosis and determine their correlation with audiometric findings and surgical outcome in a nonendemic population. We retrospectively reviewed 17 patients from August 2011 to August 2013 with surgically confirmed otosclerosis who underwent preoperative high-resolution CT scans and pre- and postoperative audiomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…1121 Of note, Png et al . 22 recently found no relationship between tomographic and audiometric findings in this setting. These conflicting results may be a result of different sample sizes or otosclerosis phases across the studies, and diverse ethnicities in the populations studied.…”
Section: Introductionmentioning
confidence: 68%
See 2 more Smart Citations
“…1121 Of note, Png et al . 22 recently found no relationship between tomographic and audiometric findings in this setting. These conflicting results may be a result of different sample sizes or otosclerosis phases across the studies, and diverse ethnicities in the populations studied.…”
Section: Introductionmentioning
confidence: 68%
“…However, when cases with multiple and simultaneous topographic involvements were analysed, especially when the endosteum and the round window were involved, some associations between audiometric and tomographic data were identified. A retrospective study by Png et al, 22 carried out in a population without endemic otosclerosis, found no significant correlation between the densitometry of the foci on high-resolution CT and the audiometric findings of average air conduction threshold, bone conduction threshold or air-bone gap.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation